IMPLEMENTASI PASAL 37 AYAT (3) PERATURAN OTORITAS JASA KEUANGAN NOMOR 29 TAHUN 2014 TENTANG PENYELENGGARAAN USAHA PERUSAHAAN PEMBIAYAAN TERHADAP EKUITAS KOPERASI DI KOTA PEKANBARU - Nurhatika Sari; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Equity in net wealth of the cooperative is cooperative entity consists of the total value of wealth invested in the cooperative owners of resources of economic cooperation or the difference between assets and liabilities. Equity in the cooperative consists of its own equity and equity loans. Pursuant to Article 37 Paragraph 3 POJK No. 29 Year 2014 Financing Company incorporated cooperative should have equity of Rp. 30,000,000,000.00 later than December 31, 2016 and Rp. 50,000,000,000.00 at the latest on December 31, 2019. This is obviously very burdensome for cooperative business activities in terms of financing to the cooperative members and non-members of cooperatives. The research objective of this thesis include: First, to determine the implementation of the equity of the cooperative are in accordance with the POJK No. 29 Year 2014 on the Implementation of the Business Financing, Second, to know the resistance of cooperatives in the city of Pekanbaru to meet equity in accordance with the POJK No. 29 Year 2014 on the Implementation of the Business Financing.The purpose of writing this essay, namely: First, whether the implementation of the equity cooperative in the city of Pekanbaru is in conformity with the POJK No. 29 Year 2014 on the Implementation of the Business Financing. Secondly, What are the barriers cooperatives in the city of Pekanbaru to meet equity in accordance with the POJK No. 29 of 2014 on the Implementation of the Business Financing?This type of research used by the author is the empirical legal research or also known as the law of sociological research, the research done by conducting the identification of the law and how the effectiveness of the law in force in the community. This research was conducted in the city of Pekanbaru, while population and sample are co-operatives in the city of Pekanbaru. In this study the data sources used, the primary data, secondary data, and the data tertiary data collecting technique in this research with interviews and literature study.From the research problem there are two main things that can be inferred First, implementation of Article 37 paragraph (3) POJK No. 29 of 2014 against the equity of cooperatives is not appropriate, because there are many cooperatives that have not qualified minimum equity. Second, barriers regarding the implementation of Article 37 paragraph (3) POJK No. 29 of 2014 due to the ignorance of the cooperative on the rules issued by the OJK on minimum equity cooperative. Where the minimum equity of Rp. The 50,000,000,000.00 in taste is very high for a cooperative. Suggestions Author, First, the Ministry of Cooperatives by the OJK is expected to conduct a review of the rules concerning the minimum equity requirements that must be owned by a cooperative incorporated, because the conditions are considered to be veryJOM Fakultas Hukum Volume III Nomor 2, Oktober 2016burdensome cooperative. Second, the Ministry of Cooperatives by the OJK is expected to be able to socialize about the POJK, especially on a minimum equity cooperative legal status.Keywords: Equity - Cooperative – Otoritas Jasa Keuangan